Application of Simulation Methods and Image Processing Techniques in Rock Blasting and Fragmentation Optimization - Qing Yang; Qidong Gao; Yongsheng Jia; Haixiao Zhou; Xin Gao; Wei Jiang; Xiaobo Ma (Applied Sciences)
Rock fragmentation is a key indicator for evaluating the effects of rock blasting and directly impacts subsequent excavation efficiency. However, predicting rock fragmentation outcomes is challenging due to the complex physical and chemical processes involved in explosive detonation. In this study, a simulation and analysis method for rock blasting fragmentation effects was developed by integrating the finite element method with image processing technology. To validate the reliability of this method, onsite blasting experiments were conducted. Furthermore, the rock blasting parameter of blast hole spacing was optimized based on this proposed method. The results showed that explosive blasting processes vary depending on the charge. Specifically, using water as a decoupling medium led to better blasting outcomes compared to air-decoupled charges. Due to the directional effects along the cylindrical charge, the explosive loading on the blast hole wall first increases and then stabilizes. The method’s feasibility is supported by the good agreement between the gradation curves of rock fragments obtained through onsite sieving tests and simulations in the 50–300 mm range. Additionally, the approach was used to optimize blasting parameters, ensuring that the fragment size distribution curve met the project requirements. Overall, this method can be used for research and analysis of rock blasting fragmentation.